Avaliação de métodos de contribuição de grupos sobre o desempenho da Equação de Peng-Robinson na avaliação do equilíbrio químico e de fases envolvendo triglicerideos, ésteres e glicerol - Arvelos, Sarah (2013)
Biodiesel replaces fully or partly common diesel and it is a renewable product. The transesterification reactions have been used to the production of biodiesel through triglycerides present in vegetable oils. Global transesterification reaction consists of reaction of one molecule of triglyceride with three molecules of alcohol having four molecules of products: three of esters (biodiesel) and one of glycerol. One way of producing biodiesel is without use of catalysts. In this route, the conditions of transesterification reaction are above the critical temperature and pressure of pure alcohol: it is the so-called supercritical route. This route provides high yields, but the experiments in the literature indicate that are required high temperature and pressure and large excess of alcohol to these high yields are achieved; these conditions prevent an economic or industrial use of this route. This study aims to determine the best set of methods for the estimation of the properties necessary for calculations of chemical equilibrium of the transesterification reaction taking into consideration that these properties need to be investigated. In addition, the goal of this study is to make the analysis of chemical equilibrium compositions in the transesterification reaction of evaluating theoretically optimal conditions. It also aims to evaluate the phase equilibrium of the transesterification reaction mixture. In set of estimation methods evaluated, the main methods for estimating properties were Constantinou-Gani method for estimating the normal boiling and vaporization enthalpy; Marrero-Gani method for the critical volume and standard state enthalpy of formation, Reidel method for vapor pressure when the normal boiling is defined; Jöback-Reid method for the heat capacity of gas and standard state Gibbs energy of formation. With regard to prediction of critical properties, it was noted that the best set of data of critical temperature, critical pressure and acentric factor that represent the molecules of interest when using the pure state equation Peng-Robinson (critical temperature and pressure estimated by the method of Marrero-Gani and acentric factor by the method of Han-Peng) is not necessarily the best set to predict the behavior of these molecules in binary mixtures in liquid-vapor at high pressures. Comparing the equation of state of Peng-Robinson and equation of state and the Peng-Robinson with term of association SAFT (CPA-PR) it was noticed that the equation of state CPA-PR improves the prediction of the behavior of mixtures under conditions near the critical temperature of the alcohol. With regard to the analysis of the phase equilibrium of the transesterification reaction mixture, it was noted, by modeling, it is possible to get a homogeneous mixture (supercritical) from beginning to end of the reaction to alcohol:triglyceride molar ratios of 30:1 with temperatures around 660 K and a pressure of 131 bar. With regard to the analysis of the chemical equilibrium of the reaction, using methanol or ethanol, high yields esters are possible for any condition above 650 K and molar ratio alcohol:oil at least 20:1.